The Effect Of Special Exercises Using An Innovative Multi-Purpose Device On Russian Spin Skill On The Pommel Horse Device For Juniors (Journal of the College of Basic Education, 2024)
The study aimed to design and manufacture an innovative device that takes into account the gradation by developing the skill (Russian rotation on the pommel horse device). And preparing special skill exercises using the (innovative) device for young people. To learn about the effect of special exercises using an innovative device in the Russian spin skill on the pommel horse device for young players. The researcher used the experimental method with the two equal groups (the tight control) with the pre- and post-test due to its relevance to the nature of the research. The research sample was chosen in a deliberate way, and they are the players (the junior team in gymnastics, which numbered (8) players, their ages ranged between (11-14) years, and it is the junior category according to the classification of the Iraqi Gymnastics Federation). By (100%) of the total research community, and the main sample was divided, by random lottery, into two groups (the experimental group and the control group), each with (4) players. The main experiment lasted (4) weeks with (3) units per week, a device consisting designed and manufactured to help players develop their athletic level and skill performance on the pommel horse device in the gymnastics game, and after implementing the training program on the device The innovator The research reached the most important conclusions: - namely, that the device helped to improve the level of players during the performance of the Russian rotation and some physical abilities related to movement.